Investasi Asing & Alih Teknologi - Fitriani Jamaluddin; Fitriah Faisal; Muhammad Ashabul Kahfi (VERITAS, 2022)
As a developing country, Indonesia requires a large enough capital to carry out national development. The capital needed for national development is not immediately available, but the Government must make useful policies in order to obtain large amounts of capital. One of the policies that can help Indonesia to obtain a large enough capital is the policy in the field of investment in the form of direct investment